2019
DOI: 10.1155/2019/6037191
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Membrane Positioning in the Surgical Treatment of Temporomandibular Joint Degenerative Disorder

Abstract: Background. Temporomandibular joint (TMJ) arthritis is a degenerative pathology that may cause pain and dysfunction. Nonsurgical therapy is the traditional treatment of TMJ diseases but if ineffective, TMJ surgery can be performed and may include arthroplasty with interposition of autograft. The encouraging results reported with the use of human amniotic membrane (HAM) in different surgical fields have highlighted its potential, but approaches providing the positioning of HAM within the intra-articular space o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…(Kesting et al 2014) This feature makes HAM suitable in oral and maxillofacial surgery, where it has been used since 1969 for the management of mucous defects after resection of malignant or precancerous lesions, due to the closure of oro-antral communication, for guided bone regeneration, post-traumatic orbital surgery and temporomandibular joint surgery. (Guarda-Nardini et al 2019;Kesting et al 2014) The present work carries on what had already been proposed in a case report (Ragazzo et al 2018) of the Authors of this paper. Because the main pharmacologic effect of BP is inhibition of osteoclasts and of bone vascularization, HAM was expected to stimulate both soft tissue healing and bone remodeling, thus contributing to the successful treatment of MRONJ.…”
Section: Discussionmentioning
confidence: 83%
“…(Kesting et al 2014) This feature makes HAM suitable in oral and maxillofacial surgery, where it has been used since 1969 for the management of mucous defects after resection of malignant or precancerous lesions, due to the closure of oro-antral communication, for guided bone regeneration, post-traumatic orbital surgery and temporomandibular joint surgery. (Guarda-Nardini et al 2019;Kesting et al 2014) The present work carries on what had already been proposed in a case report (Ragazzo et al 2018) of the Authors of this paper. Because the main pharmacologic effect of BP is inhibition of osteoclasts and of bone vascularization, HAM was expected to stimulate both soft tissue healing and bone remodeling, thus contributing to the successful treatment of MRONJ.…”
Section: Discussionmentioning
confidence: 83%
“…44 The most recent case report described the implantation of a cryopreserved amniotic patch as a disc-replacing graft after TMJ discectomy in a 48-year-old woman with TMJ DD. 15 At 3 months postoperatively, she had reported no pain and overall improvement. The investigators concluded that the results were encouraging and that the use of the placental tissue should be considered in the treatment of TMJ disease.…”
Section: Connelly Et Almentioning
confidence: 94%
“…The investigators concluded that the results were encouraging and that the use of the placental tissue should be considered in the treatment of TMJ disease. 15 Overall, the number of studies using interpositional tissue grafts for TMJ reconstructive procedures has been low. The high heterogenicity in patient populations, types of grafts used, and surgical techniques have made it difficult to draw comparisons among the reported studies.…”
Section: Connelly Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Human amniotic membrane (HAM) was positioned between the bone surfaces to replace the extracted disc. 26 , 27 , 28 The discs were stored in formalin (4% formaldehyde) and sent to the pathological anatomy department for histological analysis. The samples were cut into 3 micron‐thick sections from the formalin‐preserved, paraffin‐embedded tissues.…”
Section: Methodsmentioning
confidence: 99%